Defining the architecture of the human TIM22 complex by chemical crosslinking. Issue 2 (13th November 2020) - Valpadashi, Anusha; Callegari, Sylvie; Linden, Andreas; Neumann, Piotr; Ficner, Ralf; Urlaub, Henning; Deckers, Markus; Rehling, Peter
Abstract : The majority of mitochondrial proteins are nuclear encoded and imported into mitochondria as precursor proteins via dedicated translocases. The translocase of the inner membrane 22 (TIM22) is a multisubunit molecular machine specialized for the translocation of hydrophobic, multi‐transmembrane‐spanning proteins with internal targeting signals into the inner mitochondrial membrane. Here, we undertook a crosslinking‐mass spectrometry (XL‐MS) approach to determine the molecular arrangement of subunits of the human TIM22 complex. Crosslinking of the isolated TIM22 complex using the BS3 crosslinker resulted in the broad generation of crosslinks across the majority of TIM22 components, including the small TIM chaperone complex. The crosslinking data uncovered several unexpected features, opening new avenues for a deeper investigation into the steps required for TIM22‐mediated translocation in humans. Abstract :